GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 553 species occurrences available in GBIF matching the query: TaxonKey: Phylloscopus plumbeitarsus Swinhoe, 1861. The dataset includes 553 records from 16 constituent datasets: 11 records from Field Museum of Natural History (Zoology) Bird Collection. 25 records from Museum of Comparative Zoology, Harvard University. 1 records from CAS Ornithology (ORN). 480 records from EOD - eBird Observation Dataset. 8 records from Natural History Museum (London) Collection Specimens. 9 records from Macaulay Library Audio and Video Collection. 3 records from NMNH Extant Specimen and Observation Records. 4 records from Collection Ornithologie - SNSD. 1 records from UWBM Ornithology Collection. 1 records from Bird collection of National Museum of Nature and Science. 1 records from Naturalis Biodiversity Center (NL) - Aves. 1 records from Collection Aves (bird skins) SMF. 1 records from Geographically tagged INSDC sequences. 1 records from Norwegian Species Observation Service. 3 records from KUBI Ornithology Collection. 3 records from Bird Collection of Museum and Institute of Zoology PAS. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences